PENGEMBANGAN BLUEPRINT IT DENGAN ZACHMAN FRAMEWORK DI STP TRISAKTI - Bambang Widodo; Suharjito Suharjito (Faculty of Computer Science Universitas Indonesia, 2017)
The goals of the thesis were to create a model enterprise architecture strategic planning of IS / IT college in the form of IT blueprint with Zachman framework in STP Trisakti. Data were compiled by the main supporting documentation college events, questionnaires, interviews and field observations. Development of IT blueprint is done by utilizing the methodology of Ward & Peppard framework and EA (Enterprise Architecture) Zachman Framework is mapped into the Framework as the ultimate form of IT blueprint. Data were analyzed using analysis tools for internal and external environment. Internal environmental analysis using Value Chain, CSF (Critical Success Factor), the current application portfolio and Asset / IT, while the external environment analysis using the PEST (Political, Economic, Social, Technological), Porter's five force and the latest technology trends. It also carried defining enterprise architecture in the form of business architecture, data architecture, application architecture and technology architecture. Results of the Analysis were a blueprint IT shaped matrix cell 36 Zachman. It can be concluded that the can are 5 stages of implementation in the IT blueprint STP Trisakti with three major central system development in four areas of development of the IS / IT is the application portfolio, HR IT, Hardware, Software and Networking